To avoidance or approach: Unraveling hospitality employees' job crafting behavior response to daily customer mistreatment. (December 2022) - Lu, Wenzhu; Liu, Shanshi; Wu, Haibo; Wu, Kunjin; Pei, Jialiang
Abstract: Although multiple studies have documented the devastating effects of customer mistreatment on individuals' behaviors and attitudes, few studies have focused on employees' proactive job crafting behavior in response to customer mistreatment. Grounded in the conservation of resource (COR) theory and job crafting literature, this study addresses this concern and predicts that hospitality employees who encountered customer mistreatment will engage in both avoidance job crafting and approach job crafting behavior, leading to a distinct effect on job performance. We also predict that organizational identification could moderate the effect of customer mistreatment on employees' job crafting behavior. The results of a nine-day daily diary survey of 83 hospitality employees indicated that customer mistreatment could negatively influence job performance through avoidance job crafting behavior and could positively influence job performance through approach job crafting behavior. Organizational identification weakens the link between customer mistreatment and avoidance job crafting, whereas it strengthens the link between customer mistreatment and approach job crafting. Theoretical and practical implications for hospitality managers have been discussed.